PERFORMANCE OF LOW-COST SOLAR WATER HEATER - Ridwan, Abrar; Abdurrahman, Ridwan; Fudholi, Ahmad (Fakultas Teknik UMRI, 2022)
This study investigated the performance of a low-cost solar water heater (SWH). The SWH consists of a solar collector with a simple flat plate thermosiphon and water tank. The solar collector has, a glass cover, painted black on an aluminium absorber plate, water pipes and the sides insulated. During the testing process, the temperatures in the SWH were recorded at 1-second intervals by using Advantech Software DAQ Navi Data Logger, which is connected to a laptop via USB-4718, 8-Channel Thermocouple Input Module. The results that the efficiency of the solar collector ranged from 5% to 23%, with an average of 16% at water flow rate of 0.0019 kg/s. In addition, the time required by low-cost SWH to heat the water in a tank of 20 liters to reach its maximum temperature of 48.3°C is 8 hours 36 minutes